2007
DOI: 10.1038/nature05682
|View full text |Cite
|
Sign up to set email alerts
|

Doushantuo embryos preserved inside diapause egg cysts

Abstract: Phosphatized microfossils in the Ediacaran (635-542 Myr ago) Doushantuo Formation, south China, have been interpreted as the embryos of early animals. Despite experimental demonstration that embryos can be preserved, microstructural evidence that the Doushantuo remains are embryonic and an unambiguous record of fossil embryos in Lower Cambrian rocks, questions about the phylogenetic relationships of these fossils remain. Most recently, some researchers have proposed that Doushantuo microfossils may be giant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(185 citation statements)
references
References 22 publications
4
175
1
5
Order By: Relevance
“…Post-Sturtian but pre-Marinoan biology remains poorly documented, so it is hard to know whether inferred extinctions accompanied Sturtian or Marinoan glaciation. Available data also suggest that the major biological reorganization represented by ECAP microfossils occurred well after Marinoan deglaciation, in association with mid-Ediacaran redox change (Fike et al, 2006;Canfield et al, 2007;McFadden et al, 2008), animal radiation (Peterson and Butterfield, 2005;Yin et al, 2007), or the Acraman impact event (Grey et al, 2003). To the extent that at least some ECAP fossils preserve egg or diapause cysts of early metazoans (Yin et al, 2007), the ECAP radiation may signal the expansion of animals with resting stages in their life cycles (Marcus and Boero, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-Sturtian but pre-Marinoan biology remains poorly documented, so it is hard to know whether inferred extinctions accompanied Sturtian or Marinoan glaciation. Available data also suggest that the major biological reorganization represented by ECAP microfossils occurred well after Marinoan deglaciation, in association with mid-Ediacaran redox change (Fike et al, 2006;Canfield et al, 2007;McFadden et al, 2008), animal radiation (Peterson and Butterfield, 2005;Yin et al, 2007), or the Acraman impact event (Grey et al, 2003). To the extent that at least some ECAP fossils preserve egg or diapause cysts of early metazoans (Yin et al, 2007), the ECAP radiation may signal the expansion of animals with resting stages in their life cycles (Marcus and Boero, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Grey (2002) noted that earlier Ediacaran microfossil assemblages "are poorly known but are similar to pre-glacial ones except that there are fewer species." Similarly, in China, diverse acanthomorphic acritarchs of the middle and upper Doushantuo Formation are preceded by simpler and less diverse microfossils, with uncommon acanthomorphs appearing just below an ash bed dated by U-Pb on zircons as 632.5±0.5 million years (Condon et al, 2005;McFadden et al, 2006McFadden et al, , 2008Zhou et al, 2007;Yin et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…1B). Fossil embryos, purported bilaterians, and multicellular algae have been found in the Doushantuo Formation at the Miaohe (Xiao et al, 2002) and Jiulongwan sections in the Yangtze Gorges (Xiao, 2004;Yin et al, 2007;McFadden Fig. 1.…”
Section: Geological Settingmentioning
confidence: 99%
“…Most Marinoan glacial deposits are directly overlain by "cap carbonates" with peculiar sedimentary features and negative carbon isotope signatures (Kennedy, 1996;Hoffman et al, 1998;James et al, 2001;Hoffman and Schrag, 2002;Jiang et al, 2003a;Frimmel and Folling, 2004;Shields et al, 2007a, b;Zhou and Xiao, 2007;Shen et al, 2008), implying severe and rapid climatic changes which are thought to serve as an 'environmental filter' for biological evolution (Hoffman et al, 1998;Runnegar, 2000;Hoffman and Schrag, 2002). Strata above these postglacial cap carbonates contain the Earth's earliest multi-cellular organisms interpreted as early Metazoans (Xiao et al, 2002;Xiao, 2004;Yin et al, 2007;McFadden et al, 2008;Yuan et al, 2011). These cap carbonates have been of special interest, understandably, as they may provide significant hints about the link between the earliest diversification of animals and the most severe glaciation in Earth's history.…”
Section: Introductionmentioning
confidence: 99%
“…Such a preservation of the 40-nm-thick cell wall of Gram-negative bacteria has also been evidenced recently in phosphorite samples from Morocco dating from the Paleocene (Cosmidis et al 2013). Embryos of eukaryotes could be preserved as well in the laboratory at different development stages by phosphatization, simulating what likely occurred during the fossilization of the famous~630 Ma old Doushantuo embryos (e.g., Yin et al 2007). While some organic carbon might be degraded during these processes, it has been shown that most of it can be preserved within resulting mineralized microfossils (e.g., Benzerara et al 2004b).…”
Section: Overviewmentioning
confidence: 99%